Comparative Study: Formative Assessment Based on Numeracy Literacy and Project Results in Social Statistics Lectures - Siti Khoiruli Ummah; Alfiani Athma Putri Rosyadi; Aulia Firdaus Azzahra; Iindarti Iindarti; Joshua Abah (Universitas Islam Ahmad Dahlan (UIAD), 2025)
Formative assessments are important to determine learning success. There are many types of formative assessments, including numeracy literacy and project types. This research aimed to quantitatively analyze the differences in numeracy literacy-based formative assessments and project results during Social Statistics lectures. The research method used was descriptive with a quantitative approach. The research instrument used was the results of a formative assessment in the form of the Mid-Semester Examination.. Data analysis used descriptive statistical tests to present data and inferential statistics from the research sample, namely students of the 4th Semester 2023 Communication Science Study Program. Based on the results of descriptive statistics, the average results of the experimental class were higher than those of the control class. The results showed that the results of the formative assessment were normally distributed and homogeneous. The results of inferential statistical tests show that there is a significant difference between the test results in the experimental class and the control class. The next research recommendation is to design lectures using learning models that are relevant to numeracy literacy-based formative assessments